The hidden : a novel - Golding, Melanie (Crooked Lane, 2021)
While investigating the brutal attack on Gregor, a seemingly single man, DS Joanna Harper discovers that her estranged daughter Ruby is somehow involved in this case that is steeped in Celtic mythology.